2019
DOI: 10.1002/ehf2.12503
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the IRON‐CRT trial: effect of intravenous ferric carboxymaltose on reverse remodelling following cardiac resynchronization therapy

Abstract: Aims Iron deficiency is common in heart failure with reduced ejection fraction (HFrEF). In patients with cardiac resynchronization therapy (CRT), it is associated with a diminished reverse remodelling response and poor functional improvement. The latter is partially related to a loss in contractile force at higher heart rates (negative force-frequency relationship). Methods and resultsThe effect of intravenous ferric carboxymaltose on reverse remodelling following cardiac resynchronization therapy (IRON-CRT) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…However, further research will be necessary to provide definite answers. For instance, the IRON‐CRT trial is currently evaluating whether FCM is capable of improving LVEF and cardiac remodelling in patients with HF and reduced ejection fraction with an incomplete response to cardiac resynchronization therapy 23 . A planned echocardiographic substudy of the EFFECT‐HF study will also provide valuable information on this topic 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, further research will be necessary to provide definite answers. For instance, the IRON‐CRT trial is currently evaluating whether FCM is capable of improving LVEF and cardiac remodelling in patients with HF and reduced ejection fraction with an incomplete response to cardiac resynchronization therapy 23 . A planned echocardiographic substudy of the EFFECT‐HF study will also provide valuable information on this topic 24 .…”
Section: Discussionmentioning
confidence: 99%
“…iron in HF patients with ID. The IRON-CRT trial [93] will determine the effect of FCM on cardiac reverse remodelling and cardiac contractility in HFrEF patients. Furthermore, ongoing FAIR-HFpEF trial (ClinicalTrials.gov Identifier: NCT03074591) will verify any benefits of i.v.…”
Section: Iron-hfmentioning
confidence: 99%
“…Furthermore, while renal disease was an exclusion criteria in the major CRT trials and early observational data suggested less reverse remodelling in patients with chronic kidney disease stage IV and V, 1,3–6,47 more recent data indicate that patients with chronic kidney disease derive similar mortality benefit from lesser reverse remodelling 31,45 . Iron deficiency, which is common in CRT recipients (around 55%), might be associated with less functional improvement and less reverse remodelling following CRT, 85 possibly due to the role of iron as an essential co‐factor for protein synthesis and normal cell functioning 86 …”
Section: Action Plan For Referral and Optimization Of Cardiac Resynchmentioning
confidence: 99%
“…31,45 Iron deficiency, which is common in CRT recipients (around 55%), might be associated with less functional improvement and less reverse remodelling following CRT, 85 possibly due to the role of iron as an essential co-factor for protein synthesis and normal cell functioning. 86 In conclusion, CRT selection and optimization must occur in the context of other heart failure interventions and other comorbidities. With a growing heart failure treatment armamentarium, this is becoming increasingly challenging for the cardiologist, highlighting the need for early referral to a heart failure management team.…”
Section: Role Of Comorbiditiesmentioning
confidence: 99%